The Structural Budget Balance The IMF's Methodology - Hagemann, Robert (Washington, D.C. : International Monetary Fund, 1999)
This paper describes the methodology used by the IMF staff to calculate the structural budget balance, estimates of which are published regularly in the IMF's World Economic Outlook. The structural budget balance is the government's actual fiscal position purged of the estimated budgetary consequences of the business cycle, and is designed in part to provide an indication of the medium-term orientation of fiscal policy. Interpretation of the structural budget balance requires caution in several respects, however, some of which are reviewed in the paper. The paper then considers briefly the potential usefulness of the structural budget balance as a tool for enforcement--under the Stability and Growth Pact--of the European Economic and Monetary Union reference value on the deficit specified in the Maastricht Treaty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet